2009
DOI: 10.1007/s00540-009-0766-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of the free radical scavenger edaravone against glutamate neurotoxicity in nearly pure neuronal culture

Abstract: Edaravone mainly showed a prophylactic effect on neurons against glutamate neurotoxicity, possibly through the inhibition of necrosis via the suppression of ROS production. However, for a protective effect, a higher, supraclinical concentration was required, compared to the concentrations producing a protective effect in glial and endothelial cells in previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…We used affinity-purified primary antibodies raised against the following molecules (species immunized): MGL (rabbit; see below), DGL␣ [rabbit ], mGluR5 [guinea pig and goat (Uchigashima et al, 2007a)], MAP2 [rabbit and goat ], synaptophysin [guinea pig ], CB 1 receptor [guinea pig (Fukudome et al, 2004)], calretinin [mouse (MAB1568; Millipore Bioscience Research Reagents), rabbit (Miyazaki et al, 2011)], VGluT1 [rabbit and goat (Miyazaki et al, 2003;Miura et al, 2006)], VGluT2 [guinea pig and goat (Miyazaki et al, 2003;Miura et al, 2006)], vesicular inhibitory amino acid transporter [VIAAT; goat (Miyazaki et al, 2003;Miura et al, 2006)], vesicular acetylcholine transporter [VAChT; rabbit ], glial fibrillary acidic protein [GFAP; guinea pig (Hisano et al, 2009)], GLAST [goat (Shibata et al, 1997)], 2Ј,3Ј-cyclic nucleotide 3Ј phosphodiesterase (CNPase; mouse; C5922; Sigma), and Iba1 (rabbit; Wako). For production of the MGL antibody, a cDNA fragment encoding the N-terminal 35 amino acids (NCBI reference sequence NM_011844) was subcloned into BamHI/EcoRI site of pGEX4T-2 plasmid (GE Healthcare) for expression of glutathione S-transferase fusion proteins.…”
Section: Methodsmentioning
confidence: 99%
“…We used affinity-purified primary antibodies raised against the following molecules (species immunized): MGL (rabbit; see below), DGL␣ [rabbit ], mGluR5 [guinea pig and goat (Uchigashima et al, 2007a)], MAP2 [rabbit and goat ], synaptophysin [guinea pig ], CB 1 receptor [guinea pig (Fukudome et al, 2004)], calretinin [mouse (MAB1568; Millipore Bioscience Research Reagents), rabbit (Miyazaki et al, 2011)], VGluT1 [rabbit and goat (Miyazaki et al, 2003;Miura et al, 2006)], VGluT2 [guinea pig and goat (Miyazaki et al, 2003;Miura et al, 2006)], vesicular inhibitory amino acid transporter [VIAAT; goat (Miyazaki et al, 2003;Miura et al, 2006)], vesicular acetylcholine transporter [VAChT; rabbit ], glial fibrillary acidic protein [GFAP; guinea pig (Hisano et al, 2009)], GLAST [goat (Shibata et al, 1997)], 2Ј,3Ј-cyclic nucleotide 3Ј phosphodiesterase (CNPase; mouse; C5922; Sigma), and Iba1 (rabbit; Wako). For production of the MGL antibody, a cDNA fragment encoding the N-terminal 35 amino acids (NCBI reference sequence NM_011844) was subcloned into BamHI/EcoRI site of pGEX4T-2 plasmid (GE Healthcare) for expression of glutathione S-transferase fusion proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The medium was changed every third day and the cells were grown for 14 days. A pilot study showed that the proportion of neurons among the cells was over 90% in our culture system [15].…”
Section: Methodsmentioning
confidence: 99%
“…The relative frequencies of apoptotic cells were examined after 24 h of hypoxia at 37, 33, and 30°C by the methods of Shimizu et al as described before [15]. The cells were stained for 30 min at 37°C with Hoechest 33342 (SigmaAldrich) and propidium iodide (Sigma-Aldrich).…”
Section: Percentages Of Viable Apoptotic and Necrotic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on the mechanism of spinal cord injury suggest that free radicals affect the development of the spinal cord injury by enhancing partial ischemia-reperfusion injury (Sun et al, 2010;He et al, 2010;Wang et al, 2011). Edaravone is a radical scavenger (Uji et al, 2008;Hisano et al, 2009;Ye et al, 2011;Ono et al, 2011). The current study aimed to observe the effect of edaravone on the repair of rat spinal cord injury and to explore the potential of the combination of edaravone with neural stem cell (NSC) transplantation to treat spinal cord injury.…”
Section: Introductionmentioning
confidence: 94%